STRATEGIES OF SUBTITLING SCIENCE FICTION FILM - Jaka Pratama, - (2006)
This paper investigates subtitling strategies used in science fiction film "The Day After Tomorrow" and analyzes theirs strengths and weaknesses. The researcher employed qualitative research design characterizing principles of descriptive method. The researcher analyzed all dialogues using subtitling strategies of Gottlieb (In Taylor 2000). To find out the strengths and weaknesses, the researcher compared subtitling strategies from Gottlieb (In Taylor 2000) to translation procedures from Newmark (1998). The findings of the research reveal that the subtitler uses seven strategies: transfer (35.86%), condensation (18.16%), deletion (15.58%), paraphrase (13.98%), imitation (12.88%), decimation (2.06%), and expansion (l.35%). Transfer strategy is mostly used to maintain the accurateness and semantic values of the source language in order to lead the viewers easier to understand the subtitle. Reduction strategy comprising condensation, deletion and decimation is also mostly used to make the subtitle more effective and simpler without losing the essential meaning of the dialogue. It is thus recommended that subtitlers consider the space on the screen to synchronize dialogues with the image of the film.